Synopsis of Aspidepyris Evans, 1964 (Hymenoptera, Bethylidae) - Azevedo, Celso O. (Zootaxa, 2011)
Aspidepyris Evans, 1964 is an Epyrinae genus with two known Neotropical species. The taxonomic knowledge of its species is summarized. Aspidepyris austrinus Evans, 1967 and A. foveolatus Evans, 1964 are revised and illustrated. Additional taxonomic variations are added and geographic distribution is broadened. Aspidepyris is recorded from Trinidad & Tobago, Colombia, and Argentina for the first time. A key for both species is firstly provided.